2019
DOI: 10.1039/c9ob00313d
|View full text |Cite|
|
Sign up to set email alerts
|

Direct C–S bond formation via C–O bond activation of phenols in a crossover Pd/Cu dual-metal catalysis system

Abstract: A highly effective synthesis of unsymmetrical aryl sulfides was introduced under a dual-metal (Pd/Cu) catalysis system with a high turn-over number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…On basis of these preliminary studies and previous reports, [21][22][23][24][25][26][27][28] a plausible pathway for the preparation of 2a from (E)-N 0 -benzylideneacetohydrazide is proposed in (Scheme 3). Initially, Ag 2 CO 3 react with 1 to produce the intermediate (A).…”
Section: Resultsmentioning
confidence: 79%
“…On basis of these preliminary studies and previous reports, [21][22][23][24][25][26][27][28] a plausible pathway for the preparation of 2a from (E)-N 0 -benzylideneacetohydrazide is proposed in (Scheme 3). Initially, Ag 2 CO 3 react with 1 to produce the intermediate (A).…”
Section: Resultsmentioning
confidence: 79%
“…They treated aryl boronic acid 7 , free phenols 69 , S 8 , and characterized palladium immobilized on nano‐silica based particles named SiO 2 @OL@Pd (II) 70 (Scheme 32). [ 52 ]…”
Section: Metal‐catalyzed S‐arylation Reactionsmentioning
confidence: 99%
“…They treated aryl boronic acid 7, free phenols 69, S 8 , and characterized palladium immobilized on nano-silica based particles named SiO 2 @OL@Pd (II) 70 (Scheme 32). [52] In 2018, Zhao et al reported the first palladiumcatalyzed oxidative cross-coupling of arylhydrazines 71 and arene thiols 1 with O 2 oxidant and afforded diaryl sulfides 5 in good to high yields (Scheme 33). [53] S C H E M E 2 8 Nickel-catalyzed Chan-Lam cross-coupling of arylboronic acids with sulfonyl hydrazide S C H E M E 2 7 Nickel-catalyzed cross-coupling of arylboronic acids with thiophenols Betch and coworkers used a decarboxylative palladium-catalyzed reaction between electron-rich 2,6-dialkoxybenzoic acid derivatives 72 and diaryl disulfides 74 in the presence of Pd (CF 3 CO 2 ) 2 and Ag 2 CO 3 in a 65:1 mixture of 1,4-dioxane and tetramethylene sulfoxide (TMSO) (Scheme 34).…”
Section: Palladium-catalyzed S-arylationmentioning
confidence: 99%
“…With the new Pd-nanoparticle and CuI as the co-catalysts, the crosscoupling reaction of unreactive free-phenols (102) with arylboronic acids (103) performed well under optimized conditions (Scheme 38). 62 The developed catalyst [SiO 2 @OL@Pd] showed ultra-high catalytic activity with TONs up to 19 000. Recycling experiments indicated that the palladium nanoparticle catalyst could be recycled up to five times without any decrease in the activity and regioselectivities.…”
Section: 4mentioning
confidence: 99%